Impressive anaerobic adaptations in elite karate athletes due to few intensive intermittent sessions added to regular karate training - Ravier, G.; Dugue, B.; Grappe, F.; Rouillon, J. D. (Scandinavian Journal of Medicine & Science in Sports, 2009)
The aim of this study was to investigate the effects of adding a high-intensity intermittent session twice a week during a 7-week karate training (KT) on markers of aerobic and anaerobic metabolisms in elite class karate athletes. Two groups were studied: a KT group (n=8, age 20.1±0.9 years, 70.0±8.8 kg) that followed traditional KT, and a group that followed combined traditional karate and a high-intensity intermittent training (HIT group, n=9, age 24.4±3.1 years, 67.0±7.8 kg). The subjects undertook a supramaximal exercise and a maximal oxygen uptake test before and after the training. Blood lactate, pH and plasma ammonia were determined at rest, immediately at the end of the supramaximal exercise and during the recovery period at 2, 4, 6, 8, 10 and 15 min. After the training period, no changes occurred in the KT group. However, in the HIT group, the time to exhaustion, MAOD and VO2max in the maximal oxygen uptake test were significantly improved by 23.6%, 10.3% and 4.6%, respectively. A clear-cut discrepancy was observed in the time course of lactate and pH in the supramaximal test after the training in the HIT group. We observed a significantly higher peak for lactate and a lower extreme value for pH with a shorter delay of appearance. At the end of the test, the lactate concentration increased significantly (+53.7%) and pH declined significantly, when compared with the values obtained after the same test before the training period. Ammonia was not influenced. The addition of high-intensity intermittent sessions twice per week during the period of KT induced beneficial physiological adaptations in athletes, allowing improvement in the duration of intense physical exercise before a state of fatigue is reached.